The Effect of Parental Control on Cyber-Victimization in Adolescence: The Mediating Role of Impulsivity and High-Risk Behaviors - Álvarez-García, David; Núñez, José Carlos; González-Castro, Paloma; Rodríguez, Celestino; Cerezo, Rebeca (Frontiers in Psychology, 2019)
The aim of this work is to analyse the relationship between parental control and cyber-victimisation in adolescence, considering the possible mediating effect of impulsivity and high-risk internet behaviour. To that end we analysed the responses of 3360 adolescents aged between 11 and 18 (M = 14.02; SD = 1.40), from Asturias (Spain), to four previously validated questionnaires in order to measure the level of parental control over the use of the internet (restriction and supervision), along with high-risk internet behaviours, impulsivity and cyber-victimisation in the adolescents. The results show that parental control tends to have a protective effect on the likelihood of the children being victims of cyber-aggression, with impulsivity and high-risk internet behaviours as mediating variables. More specifically, parental restriction and supervision are positively related to each other; both forms of parental control are negatively related with the adolescent’s engaging in high-risk internet behaviours; supervision is negatively related with impulsivity; impulsivity is positively related with high-risk internet behaviours; and both impulsivity and high-risk internet behaviours are positively related to being a victim of cyber-aggression. The practical implications of these results are discussed.